PENGGUNAAN CHATGPT DALAM MEMBANTU PROSES TANYA JAWAB MAHASISWA: STUDI KASUS KELAS IV D PGSD UNIVERSITAS NUSA CENDANA - Gaudensius Jati Lamauran Koten; Hiwa Wonda; Marianus Kotus Seran; Maria Rosmita Takoi; Olga Nurhayati Mesah; Sermi Agnes Adu; Sindi Rotlis Magdalena Beba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancement of Artificial Intelligence (AI) technology, particularly ChatGPT, has significantly transformed learning practices in higher education. Many university students now utilize ChatGPT to assist various academic activities, including the question-and-answer process during lectures. However, excessive reliance on this technology raises concerns regarding the development of students’ critical thinking and academic independence. This study aims to examine how ChatGPT is used by fourth-semester students of Class IV D, Elementary School Teacher Education (PGSD) at Universitas Nusa Cendana (UNDANA), its perceived benefits, and its impact on the question-and-answer learning process. This study employed a qualitative approach with a case study design. Data were collected through direct observation during lectures and semi-structured interviews with students and the course lecturer. Data analysis followed the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. The findings indicate that students use ChatGPT across multiple learning contexts, including completing assignments, searching for references, preparing for discussions, and seeking rapid answers during question-and-answer sessions. The primary benefits reported include faster information retrieval, simplified explanations of complex material, increased self-confidence in answering lecturers’ questions, and improved academic communication skills. However, concerns were identified regarding potential negative impacts, namely reduced critical thinking ability and the emergence of AI dependency. Students demonstrated awareness of the need to verify ChatGPT’s responses against academic sources. It is concluded that ChatGPT serves as a beneficial supplementary learning tool, provided its use is accompanied by critical thinking, digital literacy, and continued engagement with credible academic references.